PEMANFAATAN CERITA PENDEK SEBAGAI MEDIA PEMBELAJARAN PADA MATERI GAGASAN POKOK DAN GAGASAN PENDUKUNG PARAGRAF - Eliana, Neneng (Jurnal Pendidikan Dasar, 2021)
Based on field observations, the use of text sourced from textbooks as a learning medium on the subject matter of the main ideas and supporting paragraph ideas as well as the application of learning methods that are less attractive by the teacher, has not been able to attract reading interest and activate students. This has an impact on the low level of student understanding and mastery of the learning material. The method used in this study is an integrative literature review that combines various studies of relevant books and journals. This study aims to provide insight to teachers about the use of short stories in learning. Based on the results of the discussion, the use of short stories in learning based on various sources can increase reading interest and activate students. so as to improve understanding and student learning outcomes. Thus, it can be concluded that short stories can be used as a medium of learning in the subject matter of the main ideas and ideas supporting paragraphs.